Methodology of justification of tactical and technical requirements for movable means of repairing arms and military equipment - Володимир Дачковський (Social Development & Security, 2019)
An analysis of the qualitative and quantitative state of mobile repair equipment, which are armed with repair units (military units), shows that the existing park consists mainly of samples that were designed in the 70's. The main disadvantage of these is the physical and moral aging and the lack of compliance with the requirements for weapons renewal systems and military equipment. Accordingly, there are drawbacks and inconsistencies between the need for repair work and the production capabilities of rolling stock.